Things To Do During Time of War. - Jaffe, Harold (Fiction International, 2004)
The article presents the poem "Things To Do During the Time of War," by Harold Jaffe. First Line: Wednesday, six-fifty a.m. Last Line: Mix with a teaspoon of chamomile tea.